C−O Hydrogenolysis of Tetrahydrofurfuryl Alcohol to 1, 5‐Pentanediol Over Bi‐functional Nickel‐Tungsten Catalysts. Issue 20 (26th September 2018) - Soghrati, Elmira; Kok Poh, Chee; Du, Yonghua; Gao, Feng; Kawi, Sibudjing; Borgna, Armando
Abstract: In this study, we report a series of bimetallic Ni−WOx catalyst for the ring‐opening of THFA into 15PDO. The structure‐performance relationship of the catalysts was discussed based on extensive characterization using techniques such as BET, H2 ‐TPR, NH3 ‐TPD, Pyr‐IR, IPA‐TPD‐MS, XRD, XPS and EXAFS/XANES. The acidity measurements show that higher W density leads to the higher amount of acid density, which could be assigned to the creation of Lewis acid sites mainly on the surface of the calcined catalysts. H2 ‐TPR profiles of Ni−WOx catalysts show that there is a strong interaction between Ni and W species, enhancing the reducibility of WOx . XRD measurements of calcined Ni−WOx catalysts reveal that the dispersion of Ni particles is enhanced after addition of WOx species. After reduction, different peaks corresponding to metallic Ni and WO3−x are identified for 10Ni−WOx catalysts, as well as new peak assigned to Ni−W intermetallic phase on 10Ni−30WOx catalyst. The formation of Ni−W intermetallic phase was further proved using XPS and EXAFS studies. THFA hydrogenolysis was also conducted under aqueous‐phase conditions over Ni−WOx catalysts, yielding up to 47 % selectivity to 15PDO, along with a highest combined C5 polyols (i. e., 15PDO and 125PTO) selectivity of approximately 64 %. However, the Ni−WOx catalytic system suffers from deactivation process due to the hydrothermal dissolution of the active phase. Further investigation reveals the better stability of metallic tungsten and Ni−W intermetallic phase (Ni4 W) against leaching since their corresponding peaks in the XRD patterns of spent catalysts remains nearly unchanged. Finally, 1, 4‐dioxane as an organic solvent was employed in THFA hydrogenolysis reaction, resulting in different product distribution, with a THP yield of around 54 %. The catalyst crystalline structure is preserved because of very low Ni and W leaching when 1, 4‐dioxane is used as solvent. Abstract : Intermetallic decoration : Bi‐functional Ni−WOx catalysts exhibit high catalytic activity towards the selective hydrogenolysis of tetrahydrofurfuryl alcohol to 1, 5‐pentanediol, along with 1, 2, 5‐pentanetriol and tetrahydropyran. Ni4 W intermetallic phase formation offers a new approach to stabilize the catalyst against leaching.